Antineutrophilic cytoplasmic antibody-associated vasculitis with hypocomplementemia has a higher incidence of serious organ damage and a poor prognosis. Issue 37 (September 2016) - Fukui, Shoichi; Iwamoto, Naoki; Umeda, Masataka; Nishino, Ayako; Nakashima, Yoshikazu; Koga, Tomohiro; Kawashiri, Shin-ya; Ichinose, Kunihiro; Hirai, Yasuko; Tamai, Mami; Nakamura, Hideki; Origuchi, Tomoki; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: A relationship between antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and complement has been shown, and complement has an important role in the pathogenesis of AAV. The clinical characteristics of AAV with hypocomplementemia still remain unclear. We conducted an observational study of 81 patients with AAV (median onset age 71 years; 58% female). Using medical records, we analyzed the patients' baseline variables, laboratory data, clinical symptoms, and therapeutic outcomes after treatments including episodes of relapses, initiation of dialysis, and death. We defined hypocomplementemia as the state in which at least one of the following was lower than the lower limit of the normal range: complement 3 (C3), complement 4 (C4), and total complement activity (CH50). Sixteen patients (20%) had hypocomplementemia at their diagnosis of AAV. Compared to the AAV patients without hypocomplementemia (n = 65), those with hypocomplementemia had significantly higher rates of the occurrence of skin lesions (8 [50%] vs. 8 [12%], P = 0.002), diffuse alveolar hemorrhage (DAH) (6 [38%] vs. 5 [8%], P = 0.006), and thrombotic microangiopathy (TMA) (3 [19%] vs. 0 [0%], P = 0.007). The AAV patients with hypocomplementemia had significantly lower platelet levels (16.5 × 10 4 vs. 24.9 × 10 4 cells/μL, P = 0.023) compared to those without hypocomplementemia. More positive immune complex deposits in renal biopsy specimens were seen in the AAV patients with hypocomplementemia than in those without hypocomplementemia (4 [80%] vs. 2 [18%], P = 0.036). Assessed by a log-rank test, hypocomplementemia at disease onset was significantly associated with death ( P = 0.033). Hypocomplementemia in AAV at the disease onset was a risk factor for the serious organ damage, and a life prognostic factor. It is thus very important to pay attention to the levels of complement at the diagnosis of AAV.